Design estratégico e personalidade do produto: o efeito dos estímulos sonoros do “sapato de salto” nas experiências dos usuários - Klanovicz, Cristiano Porto (Universidade do Vale do Rio dos Sinos, 2014)
In Strategic Design, the product is considered as part of a system - the Product - Service System - expanding its conception and providing design with a strategic perspective. From the perspective of Strategic Design, the point of sale, as a space of several interactions between the organization and the user, can be designed in a global way, so that individuals enjoy experiences that aim to create emotional bonds, which includes all forms user stimulation. Among the various approaches that allow working the relationship between design projects and user experience, this study adopts the perspective of Jordan (1999) on the personality of the product. This conception includes the use of a technique called Assigning Personality to Product (APP) which proposes that an understanding of the artifacts as living entities, endowed with personalities - being attributed to human personality traits associated with their aesthetic qualities. Specifically, the sound dimension of the artifact “high heel shoes" - resulting from the interaction between different types of soles with specific floors - and the attribution of personality to these sound stimuli consist on the focus of this work, which aims to explore the possibilities of qualification of the user experience in female footwear retail stores through sound, taking in consideration the understanding of the following problem: how Strategic Design, based on the understanding of the sound dimension of the personality of the product “high heel shoes", may contribute to the design on the sales point of view? To do so, we rescue visions of some authors that talk about the main issues to be addressed here: Design Strategy, Product - Service System and Design for Experience, whose focus will be the approach of Jordan (1999) with regard to the concept of "product personality". Thus , through an experimental research - carried out on the basis of sound stimuli arising from the interaction between different types of soles and floors , we intended to understand the relationship between sound and the personality of the object “high heel shoes”. These perceptions may contribute to the design of retail stores, as the sound interaction between these shoes with different types of floors can be seen as a trigger for positive experiences. The results indicate that it is possible to manipulate the personality of the product by sounds coming from the interaction between the materials used in it and in the environment. Thus, this study reinforces the importance of sound as a dimension capable of assigning personalities to the product, brokering and favoring therefore the experience involved in the iteration user-product-environment.
Keywords: Design Estratégico; Design para experiência; Personalidade do produto; Sapato de salto; Ponto de venda; Strategic Design; Design for experiment; Product personality; High heel shoes; Point of sale; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial